1986
DOI: 10.1007/bf00456119
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal involvement in the diabetes-induced loss of growth hormone and prolactin receptors in the livers of female rats

Abstract: Summary. Streptozotocin-induced diabetes causes a decrease in growth hormone and prolactin receptors in the livers of female rats, and in the serum concentration of somatomedin-C/ insulin-like growth factor-I, concomitantly with an increase in the serum testosterone levels. In this study, a possible role for adrenal androgens in the loss of receptors was examined. Rats were adrenalectomised bilaterally 3 days after the induction of diabetes with streptozotocin (100mg/kg intravenously), and livers were removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…It was reported that PRL stimulates ornithine decarboxylase (Richard 1975), somatomedin release (Francis & Hill 1975) and the production of synlactin in the liver (Mick & Nicoll 1985) and regulates the function of bile salt transporter (Ganguly 1997). In STZ-induced diabetic female rats, there is a significant correlation between the reduction in the number of PRL binding sites and the decrease in serum levels of somatomedin-C/insulin-like growth factor-I, suggesting that PRLR may be involved in somatomedin release from the liver (Bryson & Baxter 1986). Recent studies suggest that the short form of PRLR is internalized and mediates the action of PRL on the liver (Ouhtit et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that PRL stimulates ornithine decarboxylase (Richard 1975), somatomedin release (Francis & Hill 1975) and the production of synlactin in the liver (Mick & Nicoll 1985) and regulates the function of bile salt transporter (Ganguly 1997). In STZ-induced diabetic female rats, there is a significant correlation between the reduction in the number of PRL binding sites and the decrease in serum levels of somatomedin-C/insulin-like growth factor-I, suggesting that PRLR may be involved in somatomedin release from the liver (Bryson & Baxter 1986). Recent studies suggest that the short form of PRLR is internalized and mediates the action of PRL on the liver (Ouhtit et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, disturbances in the production and secretion of gonadal steroid hormones have been observed (Djursing et al 1982, Semple et al 1988. In addition, streptozotocin (STZ)-induced diabetic rats were shown to have gonadal steroid hormone disorders, such as low levels of testosterone in males and high levels of testosterone in females, which were accompanied by changes in PRL binding sites in the liver (Baxter et al 1981, Bryson & Baxter 1986). In the present study, we examined the importance of gonadal steroid hormone disorders in the regulation of hepatic PRLR gene expression in insulin-resistant diabetic mice (db+/db+) by examining the levels of PRLR mRNA using the quantitative reverse transcriptase polymerase chain reaction (RT-PCR).…”
Section: Introductionmentioning
confidence: 99%
“…Part of the GH resistance caused by excess glucocorticoids might be caused by their capacity to inhibit GHR mRNA and GH binding to hepatocytes (54,55) and to other cell types (99,100). In diabetic rats, which have increased glucocorticoids and GH resistance, adrenalectomy restores the GH-induced IGF-I response (101,102). In contrast with diabetic rats, however, adrenalectomy of fasted animals failed to reverse the fasting-induced inhibition of the early steps of the liver GH receptor-signaling pathway (74).…”
Section: Glucocorticoids and Proinflammatory Cytokinesmentioning
confidence: 99%
“…In the present study the urine MMP-2 level in the diabetic nephropathy group with heart failure was significantly lower than that of the diabetic nephropathy group without heart failure; and the urine MMP-2 level of the diabetic nephropathy group was significantly lower than that of the simple diabetes group. The decrease of MMP-2 levels in patients with diabetic nephropathy might be due to severe damage to the vascular endothelium, the increase of intercellular matrix components in the glomerular mesangial area, and the augment of urinary albumin excretion (18)(19)(20). Our results also showed that factors such as a history of smoking (yes), history of hypertension (yes), blood creatinine (abnormal increase), blood uric acid (abnormal increase), AGEs (abnormal increase), MMP-2 (abnormal decrease), and mALB (abnormally increase) were all independent risk factors affecting diabetic nephropathy patients combined with heart failure.…”
Section: Discussionmentioning
confidence: 99%